2006
DOI: 10.1093/brain/awl058
|View full text |Cite
|
Sign up to set email alerts
|

Spatially distinct and functionally independent mechanisms of axonal degeneration in a model of HIV-associated sensory neuropathy

Abstract: Sensory polyneuropathies are the most frequent neurological complication of human immunodeficiency virus (HIV) infection. Distal symmetric polyneuropathy (DSP), associated with HIV infection, is characterized by length-dependent axonal degeneration of sensory fibres. In rodent dorsal root ganglia (DRG) cultures, HIV viral envelope protein gp120 results in neurotoxicity and axonal degeneration. Since it is unknown whether the axonal degeneration is a consequence of neuronal death or whether it is due to a direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
1
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 42 publications
4
117
1
6
Order By: Relevance
“…Recent studies indicate that gp120 may induce both neuronal apoptosis and axonal degeneration in cultured rat DRG sensory neurons (Melli G et al, 2006). Binding of gp120 to CXCR4 on sensory axons may directly cause the local axonal degeneration.…”
Section: Neurotoxicity/neuroprotectionmentioning
confidence: 99%
“…Recent studies indicate that gp120 may induce both neuronal apoptosis and axonal degeneration in cultured rat DRG sensory neurons (Melli G et al, 2006). Binding of gp120 to CXCR4 on sensory axons may directly cause the local axonal degeneration.…”
Section: Neurotoxicity/neuroprotectionmentioning
confidence: 99%
“…Mixed DRG cultures were plated as above for 24 h. These DRG cultures were continuously treated with AraC (10 Ϫ6 M for 1 week), as described (Melli et al, 2006), and examined immunocytochemically with anti-S100 and anti-␤-IIItubulin Abs to assess the presence of Schwann cells. Our results showed that, after AraC treatment, Ͻ5% of cells stained for S100 in DRG cultures (Fig.…”
Section: Antibodies Inhibit Neurite Outgrowth Of Embryonic and Postnamentioning
confidence: 99%
“…In adult animals SDF-1 assumes yet another role, acting as a neurotransmitter that can stimulate DRG neuron excitability and produce pain (Bhangoo et al, 2007;Oh et al, 2001). Furthermore, the expression of CXCR4 receptors by DRG neurons or glia may act as a binding site where T-tropic strains of HIV-1 can produce neuronal excitation and pain or possibly neuronal death (Melli et al, 2006;Oh et al, 2001). Therefore, it is clear that CXCR4 signaling has an important role during the entire lifetime of a DRG neuron.…”
Section: Development Of the Nervous Systemmentioning
confidence: 99%